Pengaruh Komposisi Jenis Biji Kopi terhadap Keparahan Diskolorasi Gigi - Janto, Matthew Kennard Hery; Purnomo, Brigitta Natania Renata; Hardini, Nadia; Batubara, Lusiana (Universitas Diponegoro, 2025)
Coffee can cause discoloration in the hard tissues of teeth due to the presence of chlorogenic acid, which acts as a staining agent. Different types of coffee bean compositions have varying levels of staining agents. This study aims to investigate the influence of coffee bean composition (100% Arabica, 70%-30% Arabica-Robusta blend, 50%-50% Arabica-Robusta blend, and 100% Robusta) on the severity of tooth discoloration. This research is a quasi-experimental study with a pre-test and post-test control group design to assess the effect of coffee immersion on tooth color change (ΔE). The study involved 24 human premolar tooth samples divided into four treatment groups. Before treatment, the color of the samples was measured (pre-test data), and then the samples were immersed in a coffee solution for 48 hours. After immersion, the color of the samples was measured again (post-test data). Paired t-tests were conducted to determine the significance of differences between pre-test and post-test treatment. Subsequently, Kruskal-Wallis tests were performed to assess the significance of differences among the four treatment groups. Paired t-tests for all groups showed significant results (p < 0.05). Kruskal-Wallis tests indicated a significant difference among the four treatment groups (p < 0.05), with the highest tooth color change (ΔE) observed in the 100% Robusta coffee treatment group and the lowest color change in the 100% Arabica coffee treatment group. The composition of coffee bean types has an impact on the severity of tooth discoloration.